2017
DOI: 10.1111/ijfs.13690
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high‐pressure homogenisation on structural and functional properties of mussel (Mytilus edulis) protein isolate

Abstract: Summary In this study, the effects of high‐pressure homogenisation (HPH) treatment on structural and functional properties of mussel protein isolate (MPI) were investigated. HPH treatment did not modify the protein profiles of MPI, but caused changes in secondary, tertiary and quaternary structure. HPH treatment improved functional properties of MPI such as solubility, foaming ability, emulsifying activity and stability. This preliminary study demonstrated the potential of HPH technology to process MPI due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 51 publications
6
13
0
Order By: Relevance
“…It has been reported that the colloids such as proteins with high ZP (negative or positive) electrically stable, while proteins with lower value tend to coagulate (Greenwood & Kendall, ; Hanaor, Michelazzi, Leonelli, & Sorrell, ). Yu et al () reported lower absolute ZP of untreated oyster protein isolates, which indicates a weak repulsion among protein particles. However, acidic treatment of oyster protein isolates resulted in an increase in ZP, which in turn, improved the stability of these protein isolates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the colloids such as proteins with high ZP (negative or positive) electrically stable, while proteins with lower value tend to coagulate (Greenwood & Kendall, ; Hanaor, Michelazzi, Leonelli, & Sorrell, ). Yu et al () reported lower absolute ZP of untreated oyster protein isolates, which indicates a weak repulsion among protein particles. However, acidic treatment of oyster protein isolates resulted in an increase in ZP, which in turn, improved the stability of these protein isolates.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the colloids such as proteins with high ZP (negative or positive) electrically stable, while proteins with lower value tend to coagulate (Greenwood & Kendall, 1999;Hanaor, Michelazzi, Leonelli, & Sorrell, 2012). Yu et al (2018) reported lower absolute ZP of untreated TA B L E 2 Protein content (PC), ash content(AC), and fat content (Fc) of raw muscle (RM) and protein isolates extracted by acidic and alkaline method from male and female common carp…”
Section: Zeta Potentialmentioning
confidence: 99%
“…Different novel and non-conventional extraction methodshavebeenstudiedinrecentyears(JaramilloSánchezetal., 2018; Leong et al, 2015;Liu et al, 2018;Wang et al, 2016). Such as PEF Yun et al, 2017),high hydrostatic pressure Yu et al, 2018), ultrasounds (Ma et al, 2008), microwaves (Teh et al, 2015).…”
Section: Practical Applicationmentioning
confidence: 99%
“…Different novel and non‐conventional extraction methods have been studied in recent years (Jaramillo Sánchez, Garcia Loredo, Contigiani, Gómez, & Alzamora, ; Leong, Oey, Clapperton, Aganovic, & Toepfl, ; Liu, Zeng, Cheng, Liu, & Aadil, ; Wang, Zeng, Brennan, Brennan, & Han, ). Such as PEF (Aadil et al, ; Yun, Zeng, Brennan, & Liu, ), high hydrostatic pressure (Wang, Chen, et al, ; Yu et al, ), ultrasounds (Ma et al, ), microwaves (Teh, Niven, Bekhit, Carne, & Birch, ).…”
Section: Introductionmentioning
confidence: 99%
“…Cavitation, shear, turbulence, and temperature rise affect protein conformational structure, thereby modifying the functionalities (Dumay et al, ; Ye & Harte, ). It has been reported that HPH was performed to modify structural and functionalities of various proteins including dairy proteins (Ali et al, ; Iordache & Jelen, ; Lee, Lefèvre, Subirade, & Paquin, ; Ye & Harte, ), plant proteins (Dong et al, ; Liu & Kuo, ; Song, Zhou, Fu, Chen, & Wu, ; Sun, Dai, Liu, & Gao, ; Yang, Liu, Zeng, & Chen, ), meat proteins (Saricaoglu, Gul, Tural, & Turhan, ) and our previous findings in shellfish proteins (Yu, Cha et al, ; Yu, Wu, Cha, Qin, & Du, ; Yu, Wu, Cha, Zou et al, ). It has also been reported that HPH treatment has potential application for improving the functionality of muscle proteins in water to develop new meat‐based products in food industry (Chen, Xu, & Zhou, ; Chen, Zhou, Xu, Zhou, & Liu, ).…”
Section: Introductionmentioning
confidence: 99%